Hybrid Beamforming for millimetre Wave massive MIMO Communication: A Survey - Rajpreet Singh, Paras Chawla (International Journal of Advanced Science and Technology, 2020)
Hybrid Beamforming Massive MIMO Systems for millimetre Waves are seen as fundamentaltechnologies to meet continuously increasing demand of data traffic in near future with seamlessconnectivity and service quality. For millimetre waves communication the conventional fully digitalbeamforming techniques become impractical as they demand for high power, cost and complexity.The hybrid beamforming architecture minimizes the hardware cost, complexity, power consumptionwith nearly optimal performance which is the need of future generation equipment’s. Therefore,hybrid beamforming received significant attention form research community specifically for 5thgeneration wireless networks. This paper provides insights offundamental keypoints, hybridbeamforming structure, associated challenges anddetailed survey ofprominent research work withrespect to analog beamforming metrics, digital beamforming metrics and spectral efficiency asperformance parameter.